External determinants and financial outcomes of an eco-friendly orientation in smaller manufacturing firms - Leonidou, Leonidas C.; Thwaites, Des; Christodoulides, Paul (My University, 2016)
With the significant growth of problems relating to the natural environment, an increasing number of firms are engaged in environmentally friendly activities. This paper reports the results of a study conducted among 153 small-sized manufacturing units located in Cyprus, focusing on the external drivers and financial outcomes of their eco-friendly orientation. The findings confirmed the instrumental role of environmental regulations, environmental public concern, competitive intensity, and market dynamism in harnessing an eco-friendly orientation within the small firm. They also underline the critical role of this orientation in enhancing the firm’s financial results, although this link was found to be stronger when the firm possesses adequate resources and capabilities committed to environmental activities. Our study contributes to the literature by putting together, in a theoretically anchored, integrative, and causal fashion, concepts and ideas that touch upon important aspects of small firms’ environmental behavior that have been only tangentially studied in the past, namely the role of external forces in stimulating sensitivity to green issues, the dynamics of forming an ecological orientation within the organization, the positive link between eco-friendly thinking and financial performance, and the importance of supporting ecological actions with appropriate organizational resources/ capabilities. Critical implications for small business managers and public policymakers are also derived from the study findings.
Keywords: Environmental regulations; Environmental public concern; Small business; Eco-friendly